Using DFACTS Equipment to Reduce the Distributed Power Supply Influence on Distribution Network - YU Xiao-yan; LI Guo-ning (Journal of Harbin University of Science and Technology)
Distributed generation (DG) with undesirable location and capacity has adverse impacts on transmission losses of the distribution network，voltage stability and network reliability，which could not make full use of the renewable energy sources．In this paper, the distribution network is optimized by using distributed flexible transmission system (DFACTS), which reduces the limitation of DG position and capacity. Based on the measured data of the wind power generator, the Monte Carlo simulation is used to simulate the change of the output and load of the wind power generator at different times, and the line losses, voltage level and reliability are analyzed. Finally, the use of IEEE36 power distribution system verification shows that DFACTS equipment installed on a large number of DG distribution network can reduce the line losses, stabilize the system voltage and improve the reliability.